2013
DOI: 10.1002/we.1607
|View full text |Cite
|
Sign up to set email alerts
|

Verification and validation of an actuator disc model

Abstract: Wind turbine wake can be studied in computational fluid dynamics with the use of permeable body forces (e.g. actuator disc, line and surface). This paper presents a general flexible method to redistribute wind turbine blade forces as permeable body forces in a computational domain. The method can take any kind of shape discretization, determine the intersectional elements with the computational grid and use the size of these elements to redistribute proportionally the forces. This method can potentially reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 26 publications
2
87
0
Order By: Relevance
“…This method is based on blade element momentum theory and it is introduced by Sørensen and Shen [20] for the actuator line technique. In later work, the method is used for AD simulations by El Kasmi and Masson [8], Réthoré et al [13], Wu and Porté-Agel [17] and others. In the present work, the implementation of Réthoré et al [13] is used, which can be summarized as:…”
Section: Methods Iii: Ad Airfoil Methods (With Torque Calibration)mentioning
confidence: 99%
See 3 more Smart Citations
“…This method is based on blade element momentum theory and it is introduced by Sørensen and Shen [20] for the actuator line technique. In later work, the method is used for AD simulations by El Kasmi and Masson [8], Réthoré et al [13], Wu and Porté-Agel [17] and others. In the present work, the implementation of Réthoré et al [13] is used, which can be summarized as:…”
Section: Methods Iii: Ad Airfoil Methods (With Torque Calibration)mentioning
confidence: 99%
“…Troldborg [23] found that for modern large wind turbines with a sharp tip, c2 should be set to 27, which will be adopted in the present research. Réthoré et al [13] validated the AD with tabulated airfoil data with full rotor computations of a single NREL 5-MW reference wind turbine. Reasonable agreement was found, however, the AD with tabulated airfoil data overpredicted the tangential forces, which resulted into an overpredicted power.…”
Section: Methods Iii: Ad Airfoil Methods (With Torque Calibration)mentioning
confidence: 99%
See 2 more Smart Citations
“…The wind turbine rotor is modeled as an actuator disk (AD) using the implementation proposed by Réthoré et al (2014 use the same model to simulate the induction zone of a 500 kW turbine and validated their predictions with lidar measurements. …”
Section: Wind Turbine Modelmentioning
confidence: 99%